How Do General Practitioners (GPs) Engage in Falls Prevention With Older People? A Pilot Survey of GPs in NHS England Suggests a Gap in Routine Practice to Address Falls Prevention - Mackenzie, Lynette; McIntyre, Anne (Frontiers in Public Health, 2019)
Falls are highly prevalent amongst older people and have substantial financial and social costs for health services, the community and older people and their families. Prevention of falls is crucial to effectively managing this threat to older people. General practitioners are key health professionals to identify older people at risk of falls on their caseloads, as older people will visit them regularly. Once older people at risk of falls are identified, actions can be taken to reduce the risk of falls by referring to appropriate services available in the community, such as allied health practitioners. However, the level of engagement in evidence based falls prevention by GPs is unknown. This study aimed to explore how British general practitioners (GPs) address falls prevention with older people as a routine part of their work, and to determine if there are any gaps in practice. As a pilot study, other aims were to test the feasibility of methods to survey GPs, and to determine if a larger survey to comprehensively include a population of GPs was warranted from the findings. An on-line cross sectional survey was distributed by email to all the Clinical Commissioning Groups in NHS England (n=213) and individual general practices listed on the NHS Choices website, supplemented by invitations distributed to CCGs through Twitter and LinkedIn sites. Thirty-seven responses were received. Most GPs were unfamiliar with the 2013 NICE guidelines on assessment and prevention of falls in older people (51.4%, n=19), and only 29.7% (n=11) asked older people if they had fallen during consultations. If falls risk was identified, 81.1% (n=30) frequently made referrals to physiotherapy (PT) and 56.8% (n=21) to occupational therapy (OT). Most GPs did not identify older people on their caseloads as being at risk of falls unless they presented with a fall, and referral rates to AHPs or falls prevention programs were low. Despite the low response rate, consistent gaps in practice were identified across respondents that are of concern if successful falls prevention in primary care is to be achieved. Alternative methods are needed to access a more representative sample of GPs to confirm findings.